Impact of Key Factors on Student Satisfaction in Private Universities of Balkh Province: A Multivariate Linear Regression Analysis - Qarizada, Abdulkhaliq; Mustafa Qaderi; Farhad Bahrangi (ARMADA : Jurnal Penelitian Multidisiplin, 2025)
This study investigates the impact of key factors on overall student satisfaction in private universities in Balkh Province, Afghanistan. Five primary factors teaching quality, educational facilities, administrative management, social environment, and costs were examined as independent variables. Data were collected from 350 students using a standardized questionnaire and analyzed through multivariate linear regression in SPSS. The statistical analysis revealed that the model explains 97.7% of the variance in overall student satisfaction, indicating high explanatory power. Findings suggest that teaching quality, educational facilities, and administrative management have a significant positive impact on student satisfaction, while social environment and costs showed no significant effect. Among these, teaching quality emerged as the strongest predictor, playing a pivotal role in enhancing students’ academic experience and motivation. These results align with prior research and underscore the importance of improving educational processes and efficient management to elevate student satisfaction. Given the local context of Afghanistan and post-COVID-19 challenges, this study introduces novelty by exploring the influence of digital technology on satisfaction factors. Based on the findings, it is recommended that universities prioritize faculty development, upgrade educational facilities, and streamline administrative systems to enhance educational quality and student experience. Future research should adopt a broader approach to examine the role of costs, financial equity in education, and digital factors in student satisfaction.